Italy and Libya : from colonialism to a special relationship (1911-2021) - Monzali, Luciano; Soave, Paolo (London : Routledge, Taylor & Francis Group, 2023)
"This volume proposes a historical analysis of Italian-Libyan relations in contemporary times. After examining the colonialism of liberal Italy, which in 1911 culminated in the military campaign for the conquest of the Libyan regions, it evaluates the impact of fascism in Libya and the attempt to launch a broader pro-Arab policy. The third section analyzes the construction of the so-called 'special relationship' between Rome and Tripoli since the 50s when an economic interdependence between the Libyan oil producer and the Italian industrial power was pursued despite political differences. Finally, the volume also focuses on the dramatic implosion of Libya and the loss of its political unity following the fall of the Gaddafi regime, which on the one hand, scaled back Italy's regional role, on the other, spread instability throughout the Euro-Mediterranean area. The volume uses a historiographical methodology focused on primary sources and updated scientific literature but also includes specialized analyses of the most current scenarios. This is the first systematic work on the Italian-Libyan relationship produced in English, accessible to area scholars, specialists, analysts and students, who intend to deepen their understanding of one of the pivotal factors of the Euro-Mediterranean balance, which is currently missing"--
Foreword / by Sergio Romano -- Tripolitania and Cyrenaica in liberal Italy's foreign policy / GianPaolo Ferraioli -- History of a minority, not a minor history : the Maltese community in Tripoli from the Liberal Age to fascism / Simona Berhe -- From the 'Riconquista' to the normalisation : fascism and Libya / Paolo Soave -- The demographic colonisation in Libya 1926 -- 1940 / Federico Cresti -- If the monument could speak : Jewish Italian imaginaries across the Mediterranean / Piera Rossetto -- Pietro Quaroni, post-fascist Italy and the Libyan question 1945-1949 / Luciano Monzali -- Republican Italy and the Senussi monarchy 1951-1969 / Federico Imperato -- Aldo Moro, Italian diplomacy and Gaddafi's rise to power 1969-1978 / Giuseppe Spagnulo -- The silent friend : ENI and Gaddafi's Libya / Rosario Milano -- From troublemaker to strategic partner : Gaddafi and the West / Karim Mezran and Federica Saini Fasanotti -- Two great friends : Berlusconi and Gaddafi 1994-2011 / Ilaria Tremolada -- Libya's Arab spring And Italy's post-uprising Influence / John Davis -- Italy and the disintegration of the Libyan State / Roberta La Fortezza -- A new state-building process for Libya? : Italy and the international community 2011-2021 / Arturo Varvelli and Alessia Melcangi.
Keywords: HISTORY / General; HISTORY / Europe / Italy; HISTORY / Middle East / General; Italy -- Foreign relations -- Libya; Libya -- Foreign relations -- Italy; Italy -- Politics and government -- 1870-; Libya -- Politics and government; Italy -- Colonies -- Africa